Police Recruitment and Retention for the New Millennium - Wilson, Jeremy M.; Dalton, Erin; Scheer, Charles; Grammich, Clifford A. (RAND Corporation, 2023)
Many police departments report difficulties in creating a workforce that represents community demographics, is committed to providing its employees the opportunity for long-term police careers, and effectively implements community policing. This book summarizes lessons on recruiting and retaining effective workforces.